2013
DOI: 10.1128/jvi.02263-12
|View full text |Cite
|
Sign up to set email alerts
|

p38 and OGT Sequestration into Viral Inclusion Bodies in Cells Infected with Human Respiratory Syncytial Virus Suppresses MK2 Activities and Stress Granule Assembly

Abstract: Respiratory syncytial virus (RSV) forms cytoplasmic inclusion bodies (IBs) that are thought to be sites of nucleocapsid accumulation and viral RNA synthesis. The present study found that IBs also were the sites of major sequestration of two proteins involved in cellular signaling pathways. These are phosphorylated p38 mitogen-activated protein kinase (MAPK) (p38-P), a key regulator of cellular inflammatory and stress responses, and O-linked N-acetylglucosamine (OGN) transferase (OGT), an enzyme that catalyzes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 49 publications
(69 reference statements)
3
71
0
Order By: Relevance
“…According to this model, sequestration of O-linked N-acetylglucosamine transferase provides a mechanism for RSV to prevent stress granule assembly, since the modification of proteins with O-linked N-acetylglucosamine is an important early step in stress granule assembly (131). Sequestering host proteins in IBs to inhibit stress granule assembly is consistent with the negative correlation observed between the presence of large IBs and stress granule formation (128).…”
Section: Role Of Inclusion Bodies and Stress Granules In Rsv Infectionsupporting
confidence: 69%
See 1 more Smart Citation
“…According to this model, sequestration of O-linked N-acetylglucosamine transferase provides a mechanism for RSV to prevent stress granule assembly, since the modification of proteins with O-linked N-acetylglucosamine is an important early step in stress granule assembly (131). Sequestering host proteins in IBs to inhibit stress granule assembly is consistent with the negative correlation observed between the presence of large IBs and stress granule formation (128).…”
Section: Role Of Inclusion Bodies and Stress Granules In Rsv Infectionsupporting
confidence: 69%
“…The host proteins that colocalize with IBs include a number of antiviral, chaperone, and signaling proteins such as MAVS (124), MDA5 (124), phosphorylated p38 (128), O-linked N-acetylglucosamine transferase (128), and HSP70 (129). The presence of antiviral and signaling proteins within IBs opens up the possibility that these proteins are specifically sequestered within the inclusions to prevent host cell responses that would be unfavorable to RSV infection.…”
Section: Role Of Inclusion Bodies and Stress Granules In Rsv Infectionmentioning
confidence: 99%
“…Marburg virus (MARV), another member of the filovirus family, recruits components of the endosomal complex required for transport (ESCRT) machinery to viral inclusions to enhance budding (80). The sequestration of cellular proteins within viral inclusions, including HuR and proteins involved in antiviral signaling, was also observed in respiratory syncytial virus (RSV) infection and dampened the antiviral host response (81)(82)(83). This supports the hypothesis that the sequestration of certain cellular proteins within viral inclusions promotes viral infection by disrupting antiviral signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that M and F may interact at or near the IBs and implicated these structures in the cascade of late-stage events that lead to virions. IBs are multifunctional bodies (45,46) and are believed to represent the sites of viral replication. Coexpression of N and P is sufficient to induce formation of IBs (47).…”
mentioning
confidence: 99%